Progestin plus metformin improves outcomes in patients with endometrial hyperplasia and early endometrial cancer more than progestin alone: a meta-analysis - Shao, Fengping; Li, Yinguang; Zhao, Yunhe (Frontiers in Endocrinology, 2023)
Objective Progestin based therapy is the preferred option for fertility-sparing treatment of reproductive-age women with preserved fertility in endometrial hyperplasia (EH) or early endometrial cancer (EEC). Our objective was to investigate whether metformin could enhance the efficacy of progestin-based therapies by meta-analysis. Methods We conducted a meta-analysis of randomized or non-randomized controlled trials by searching of PubMed, Embase, Web of science, and Cochrane database from inception to November 8, 2022. The results of enrolled studies were pooled using meta-analysis to estimate the effect of progestin plus metformin on remission, recurrence, pregnancy rate and live birth rate. Results In the analysis of progestin administered systemically or locally, complete response (CR) was significantly higher in progestin plus metformin versus progestin alone in the EH group (pooled OR 2.08, 95% CI 1.29 to 3.34, P=0.003), in the EEC group (pooled OR 1.86, 95% CI 1.13 to 3.05, P=0.01), but not in EEC and EH group (pooled OR 1.46, 95% CI 0.97 to 2.21, P=0.07). In the analysis of progestin administered systemically, complete response was improved in progestin plus metformin versus progestin alone, in the EH group (pooled OR 2.47, 95% CI 1.45 to 4.21, P=0.0009), in the EEC group (pooled OR 2.09, 95% CI 1.18 to 3.71, P=0.01), and in the EEC and EH group (pooled OR 2.03, 95% CI 1.16 to 3.54, P=0.01). The relapse rates of patients with EEC and EH were not different (pooled OR 0.54, 95% CI 0.24 to 1.20, P=0.13). For obstetric outcomes, the addition of metformin improved pregnancy rate (pooled OR 1.55, 95% CI 0.99 to 2.42, P=0.05), but not live birth rate (pooled OR 0.95, 95% CI 0.45 to 2.01, P=0.89). Conclusion For fertility-sparing management, compared to progestin alone, the outcomes of patients with endometrial hyperplasia and early endometrial cancer were more improved with progestin plus metformin because progestin plus metformin increases the rate of remission and pregnancy.